Does exclusion of cancers registered only from death-certificate information diminish socio-demographic disparities in recorded survival?. (June 2017) - Tervonen, Hanna E.; Roder, David; Morrell, Stephen; You, Hui; Currow, David C.
Highlights: Socio-demographic factors were associated with Death Certificate Only (DCO) diagnosis in NSW, Australia. Nonetheless including or excluding DCOs had no discernible impact on relative socio-demographic cancer survival disparities. Further research should examine whether these findings apply in settings with higher DCO proportions. Abstract: Background: Death Certificate Only (DCO) cancer cases are commonly excluded from survival analyses due to unknown survival time. This study examines whether socio-demographic factors are associated with DCO diagnosis, and the potential effects of excluding DCO cases on socio-demographic cancer survival disparities in NSW, Australia. Methods: NSW Cancer Registry data for cases diagnosed in 2000–2008 were used in this study. Logistic regression was used to estimate the odds of DCO registration by socio-demographic sub-group (socio-economic disadvantage, residential remoteness, country of birth, age at diagnosis). Cox proportional hazard regression was used to estimate the probability of death from cancer by socio-demographic subgroup when DCO cases were included and excluded from analyses. Results: DCO cases consisted of 1.5% (n = 4336) of all cases (n = 299, 651). DCO diagnosis was associated with living in socio-economically disadvantaged areas (most disadvantaged compared with least disadvantaged quintile: odds ratio OR 1.25, 95%CI 1.12–1.40), living in inner regional (OR 1.16, 95%CI 1.08–1.25) or remote areas (OR 1.48, 95%CI 1.01–2.19), having an unknown country of birth (OR 1.63, 95%CI 1.47–1.81) and older age. Including or excluding DCO cases had no significant impact on hazard ratios for cancer death by socio-economic disadvantage quintile or remoteness category, and only a minor impact on hazard ratios by age. Conclusion: Socio-demographic factors were associated with DCO diagnosis in NSW. However, socio-demographic cancer survival disparities remained unchanged or varied only slightly irrespective of including/excluding DCO cases. Further research could examine the upper limits of DCO proportions that significantly alter estimated cancer survival differentials if DCOs are excluded.